Rapid detection of pigeon adenovirus 2 using a TaqMan real-time PCR assay - Chen, Cuiteng; Zhu, Chunhua; Chen, Zhen; Cai, Guozhang; Lin, Lin; Zhang, Shizhong; Jiang, Bin; Miao, Zhongwei; Fu, Guanghua; Huang, Yu; Wan, Chunhe (Poultry science, 2024)
Pigeons infected with aviadenoviruses have been found worldwide. Recently, pigeon adenovirus 2 (PiAdV-2) has been widely distributed in racing pigeons in Germany. However, the epidemiology of this virus remains unclear due to the lack of a specific detection platform for PiAdV-2. In this study, we first detected PiAdV-2 positivity in racing pigeons (designated FJ21125 and FJ21128, which share 100% nucleotide identity with each other based on the fiber 2 gene) in Fujian, Southeast China. These genes shared 99.8% nucleotide identity with PiAdV-2 (GenBank No. NC_031501) but only 54.1% nucleotide identity with PiAdV-1 (GenBank No. NC024474). Then, the TaqMan-qPCR assay for the detection of PiAdV-2 was established based on fiber 2 gene characterization. The established assay had a correlation coefficient of 1.00, with an amplification efficiency of 99.0%. The minimum detection limit was 34.6 copies/μL. Only PiAdV-2 exhibited a positive fluorescent signal, and no signal was detected for other pathogens (including PiCV, FAdV-4, FAdV-8a, EDSV, PPMV-1, RVA and PiHV). The assay has good reproducibility, with a coefficient of variation less than 2.42% both intragroup and intergroup. The distributions of PiAdV-2 in fecal samples from YPDS (35 samples) and healthy (43 samples) racing pigeons from different geographical areas were investigated and were 37.14% (YPDS) and 20.93% (healthy), respectively. In summary, we developed a TaqMan-qPCR platform for the detection of PiAdV-2 infection with high sensitivity, specificity, and reproducibility. We confirmed the presence of PiAdV-2 in China, and our data suggested that there is no indication of a correlation between YPDS and PiAdV-2. This study provides more information on the pathogenesis mechanism and epidemiological surveillance of PiAdV-2.